2011
DOI: 10.1002/mus.22162
|View full text |Cite
|
Sign up to set email alerts
|

Muscle function in monozygotic female twin pairs discordant for hormone replacement therapy

Abstract: Introduction: Postmenopausal monozygotic twin pairs discordant for hormone replacement therapy (HRT) provide an advantageous study design controlling for genetic background for elucidating the relationships between aging, sex hormone levels, muscle strength, contractile capacity, and fatigability. Methods: Thirteen postmenopausal monozygotic twin pairs discordant for HRT were measured for maximal voluntary torque (MVC) and twitch characteristics using electrical stimulation before and after intermittent dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…In contrast, in vivo studies in tissue samples or circulation have not been able to clearly demonstrate the effects of estrogen deficiency on pro-inflammatory cytokines. However, our previous findings showed that HRT affects the IL-6 and insulin growth factor 1 (IGF-1) pathways suggesting an association between postmenopausal HRT, healthier inflammatory and anabolic condition, together with enhanced muscle quality and performance (Ronkainen, et al 2009, Finni, et al 2011, Ahtiainen, et al 2012a, Qaisar, et al 2013. It is commonly known that postmenopausal estrogen deficiency contributes to the aging process and according to our recent findings (Ahtiainen, et al 2012a, Ahtiainen, et al 2012b, most likely to the development of age-associated low intensity inflammatory status called "inflamm-aging" (Franceschi, et al 2000).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, in vivo studies in tissue samples or circulation have not been able to clearly demonstrate the effects of estrogen deficiency on pro-inflammatory cytokines. However, our previous findings showed that HRT affects the IL-6 and insulin growth factor 1 (IGF-1) pathways suggesting an association between postmenopausal HRT, healthier inflammatory and anabolic condition, together with enhanced muscle quality and performance (Ronkainen, et al 2009, Finni, et al 2011, Ahtiainen, et al 2012a, Qaisar, et al 2013. It is commonly known that postmenopausal estrogen deficiency contributes to the aging process and according to our recent findings (Ahtiainen, et al 2012a, Ahtiainen, et al 2012b, most likely to the development of age-associated low intensity inflammatory status called "inflamm-aging" (Franceschi, et al 2000).…”
Section: Introductionmentioning
confidence: 93%
“…There are indications that dramatically decreasing level of circulating 17β-estradiol (E 2 ) at the time of menopause contributes to age-associated muscle weakness (Phillips, et al 1993, Sipila, et al 2001. Our previous studies have shown that the use of estrogen-or estrogen and progesterone -based hormone replacement therapy (HRT) is associated with better muscle quality properties, such as a positive muscle-fat ratio within the muscle compartment, as well as improved muscle performance characteristics like muscle power and mobility (Ronkainen, et al 2009, Finni, et al 2011. We also demonstrated in a one-year RCT that HRT counteracts the postmenopause-related transcriptome level changes (Pollanen, et al 2007) and that several years of HRT causes subtle but relevant changes in the muscle transcriptome in postmenopausal women .…”
Section: Introductionmentioning
confidence: 99%
“…One report examined the effects of OC consumption and withdrawal on strength 34 and one combined previous OC use with a control group that had never used OC's 35 . Undoubtedly, the most common reproductive functioning models used in the literature in the last decade were the menopause and HRT [36][37][38][39][40][41][42][43][44] . ese models were used to investigate numerous facets of muscle strength including; muscle sti ness 30 and soreness 29 , dynamic and isometric force production 38,43 , power 41 , endurance 32 , performance 33 , functional capacity 39 and gene expression 37 .…”
mentioning
confidence: 99%
“…Undoubtedly, the most common reproductive functioning models used in the literature in the last decade were the menopause and HRT [36][37][38][39][40][41][42][43][44] . ese models were used to investigate numerous facets of muscle strength including; muscle sti ness 30 and soreness 29 , dynamic and isometric force production 38,43 , power 41 , endurance 32 , performance 33 , functional capacity 39 and gene expression 37 . Generally, the relationship between oestrogen and muscle strength was positive; high concentrations of oestradiol were associated with the preservation of muscle strength and mass in addition to mobility and function [36][37][38][39][40][41][42][43][44] .…”
mentioning
confidence: 99%
See 1 more Smart Citation